Disparities in Female Pediatric, Adolescent and Young Adult Oncofertility: A Needs Assessment - Leslie Coker Appiah (MDPI AG, 2021)
Advancements in cancer screening and implementation of targeted treatments have significantly improved survival rates to 85% for pediatric and AYA survivors. Greater than 75% of survivors will live to experience the long-term adverse outcomes of cancer therapies, termed late effects (LE), that disrupt quality of life (QoL). Infertility and poor reproductive outcomes are significant disruptors of QoL in survivorship, affecting 12–88% of survivors who receive at-risk therapies. To mitigate risk, fertility preservation (FP) counseling is recommended as standard of care prior to gonadotoxic therapy. However, disparities in FP counseling, implementation of FP interventions, and screening for gynecologic late effects in survivorship persist. Barriers to care include a lack of provider and patient knowledge of the safety and breadth of current FP options, misconceptions about the duration of time required to implement FP therapies, cost, and health care team bias. Developing strategies to address barriers and implement established guidelines are necessary to ensure equity and improve quality of care across populations.